Visibility: aplicativo de mapas baseado em crowdsourcing para acessibilidade - Bronoski, Mariceli (2022)
Society is living in the age of technology and mobility, in which full connection to the Internet, from anywhere and anytime, is becoming a necessity for people. In this scenario, applications are important tools for solving everyday problems. The present study presents the process of developing an application that, integrated with a map system, allows the visualization and creation of markings of places and establishments, together with the classification of accessibility. Thus, the work aims to identify contributions to the mobility of people with disabilities, more specifically, physical-motor disabilities, through the development and implementation of an application, aimed at managing and providing information on accessibility mechanisms in the central region of the city. from Campo Mourão-PR. The interactivity of the system with users favors the collection of information about accessible places and the lack of accessibility. The Visibility Application, taking shape and undergoing usability research using the System Usability Scale (SUS) tool with a good rate, even in its test phase, seeks to present itself as another tool available in the search for accessibility in the city of Campo Mourão. Eventually, the whole city tends to benefit, since it can arouse interest in making places accessible, which contributes to the well-being not only for people with disabilities, but for everyone. Interaction is fundamental to developing smart city concepts and an important step towards expanding and consolidating accessibility concepts. This integration is essential for more and more places to become accessible, for there to be engagement and integration, seeking to incorporate accessibility into the routine of cities, not only for people with disabilities or reduced mobility, but for society as a whole.